Consumer relationship with pro-environmental apparel brands: effect of knowledge, skepticism and brand familiarity. Issue 1 (10th June 2019) - Copeland, Lauren; Bhaduri, Gargi
Abstract : Purpose: The apparel industry is often scrutinized for its lack of environmental stewardship, and thus pro-environmental initiatives have been of significant consideration among apparel brands in recent years. However, one personality trait of specific concern to brand marketers is consumer skepticism toward climate change, which has the potential to negatively impact the success of brands' pro-environmental initiatives. In this light, research indicates that knowledge of the environmental impact of products can lead to lower skepticism (Tobler et al., 2012 ) and ultimately higher purchase intentions of such products. Thus, this study investigates the impact of consumers' knowledge about environmental impact of apparel, climate change skepticism on their evaluation of brands' pro-environmental initiatives (shared value and perceived benefit) and ultimately their relationship with the brand (perceived trust, commitment), leading to purchase intention for both familiar and unfamiliar brands. Design/methodology/approach: Two separate studies were conducted for familiar and unfamiliar brands. Data for online surveys were collected from two US nationwide samples and analyzed using path analyses. Findings: Consumers' intention to purchase from a pro-environmental brand was influenced by knowledge and skepticism. Particularly, the obtained shared value perceptions and perceived benefits of consumers influenced their relationship with the brand through trust and commitment, which eventually impacted their intention to purchase from the brand. Differences were observed for familiar and unfamiliar brands. Practical implications: Findings of this study will help brand managers design effective pro-environmental marketing messages. Both familiar and unfamiliar brands would benefit from educating consumers about the true environmental impact of their apparel choices, as well as the personal benefits and values earned when purchasing/consuming pro-environmental apparel. This, in turn, reduces consumer skepticism toward climate change, leading to favorable evaluations of the brand's pro-environmental initiatives and improvement of long-term brand relations. Originality/value: This study extended the social exchange theory by understanding antecedents of consumers' shared value and perceived benefits, namely, their knowledge about the environmental impact of apparel and their skepticism toward climate change, with the final outcome variable being consumers' patronage intention of pro-environmental brands.